Islamic Rationalism: Between Tradition and Controversy - Hamzah, Hakma; Achmad Khudori Soleh; Azmi Putri Ayu Wardani (JURNAL PENELITIAN KEISLAMAN, 2024)
Long before Greek philosophy influenced Islamic thought, Islam already had a tradition of rational thinking. This study traces the role of language in the development of Islamic rationalism and addresses 19th-century Orientalists' claims that Islamic philosophy is merely an imitation of Greek philosophy. Using a qualitative library research approach, the study finds:(1) The rationalism in Islam is a genuine product of Islamic intellectual effort, rooted in the Qur'an and Hadith. The interpretation of these sources gave rise to the Islamic rational system, particularly through the study of language (nahw-sarf), proving that Islamic rationalism is an intrinsic part of its tradition.(2) The claim that Islamic rationalism is adopted from Greek thought is countered by evidence that rational thinking was practiced in Islam long before Greek philosophy's influence. Muslim philosophers further developed Greek ideas, creating a unique form of rationality known as hikmah, demonstrating that Islamic philosophy is an original intellectual tradition.